A novel approach for lithium recovery from waste lithium-containing aluminum electrolyte by a roasting-leaching process. (October 2021) - Wu, Shaohua; Tao, Wenju; Zheng, Yanchen; Ge, Hui; He, Jingui; Yang, Youjian; Wang, Zhaowen
Graphical abstract: Highlights: A route for treating spent lithium-containing aluminum electrolytes was developed. Selective extraction and separation of lithium from the spent aluminum electrolyte. Lithium was efficiently recovered as Li2 CO3 . The treated aluminum electrolytes could be returned to the aluminum smelting cell. Abstract: With the development of secondary resources, development of suitable methods for the recovery of high value metals from solid waste is crucial for sustainable development. Aluminum electrolysis of China, solid waste, such as waste aluminum electrolyte, has been largely idled and caused serious environmental pollution. In this paper, a novel approach is developed for achieving the separation/recovery of lithium from spent lithium-containing aluminum electrolyte by a sodium carbonate roasting–acid leaching process. The effect on the extraction behavior of lithium under different roasting and leaching conditions was systematically studied. X-ray diffraction (XRD) and scanning electron microscopy (SEM) were used to elucidate the phase evolution. The results indicated that 73.1% of the lithium was obtained under the optimized conditions: a m(actual)/m(theory) ratio of 1.10 with roasting at 850 °C for 2.5 h; a HNO3 solution concentration of 2 mol/L, and a liquid to solid ratio of 10 at 60 °C for 180 min. Through the analysis of the roasting sample, it was found that the addition of Na2 CO3 promoted the conversion of Na2 LiAlF6 to LiF. The content of lithium in electrolyte significantly reduced from 2.20% to 0.71% after leaching, which made it possible for the residue to be reused as the raw material for the aluminum reduction cell. The leachate was neutralized and purified with CaO and Na2 CO3 solution, respectively, and then lithium be recovered in the form of Li2 CO3 . Overall, this study highlights an effectively and environmentally feasible plan for the treatment of spent aluminum electrolyte and to recycle lithium.